2014
DOI: 10.1603/ec13369
|View full text |Cite
|
Sign up to set email alerts
|

Use of Honeydew Production to Determine Reduction in Feeding by <I>Bemisia tabaci</I> (Hemiptera: Aleyrodidae) Adults When Exposed to Cyantraniliprole and Imidacloprid Treatments

Abstract: Bemisia tabaci (Gennadius) whitefly populations produce economically important damage to crops by their direct feeding and also by transmitting plant viruses. Although there are several methods to reduce B. tabaci damage, most growers rely on the use of insecticides to decrease populations of this pest. Insecticides that reduce feeding of whitefly adults may also reduce the transmission of viruses that are harmful to crop plants. However, demonstrating the feeding reduction has proved challenging. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 17 publications
0
10
0
5
Order By: Relevance
“…Electrical penetration graphing (EPG) studies revealed reductions in probing behaviour on cyantraniliprole‐treated plants by F. occidentalis and F. fusca . Feeding reduction by cyantraniliprole has also been reported for Bemisa tabaci and D. citri , measured indirectly by the adult honeydew excretions . Similarly, B. tabaci nymphs exhibited a significant decrease in feeding on plants treated with cyantraniliprole .…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Electrical penetration graphing (EPG) studies revealed reductions in probing behaviour on cyantraniliprole‐treated plants by F. occidentalis and F. fusca . Feeding reduction by cyantraniliprole has also been reported for Bemisa tabaci and D. citri , measured indirectly by the adult honeydew excretions . Similarly, B. tabaci nymphs exhibited a significant decrease in feeding on plants treated with cyantraniliprole .…”
Section: Resultsmentioning
confidence: 78%
“…25 Feeding reduction by cyantraniliprole has also been reported for Bemisa tabaci and D. citri, measured indirectly by the adult honeydew excretions. 24,26 Similarly, B. tabaci nymphs exhibited a significant decrease in feeding on plants treated with cyantraniliprole. 27 wileyonlinelibrary.com/journal/ps More importantly, this reduction in feeding activity has been associated with a decrease in virus transmission.…”
Section: Antifeedant Effectmentioning
confidence: 97%
“…High efficacy against B. tabaci and other pests has already been described both in laboratory and in field trials . Cyantraniliprole has a significant effect on reducing insect feeding, and has been shown to reduce virus transmission …”
Section: Introductionmentioning
confidence: 94%
“…For example, imidacloprid has been shown to have anti‐feedant effects on B. tabaci that contribute to a reduction of various vectored plant viruses . Similarly, there is much evidence in support of the disruptive effect that cyantraniliprole has on feeding by various insect vectors . In the case of imidacloprid, the possibility exists that resistance to both lethal and sublethal effects has developed after 22 years of intensive use in vegetable crops and melons of the Southwest.…”
Section: Discussionmentioning
confidence: 99%